Habeas Corpus como instrumento de efetivação da tutela jurídica dos animais não humanos - Pillar, Mariana Monteiro (2025)
This research aimed to examine the limits and possibilities of extending the application of Habeas Corpus to non-human animals, conducting a qualitative analysis of Habeas Corpus rulings within the Brazilian legal system and in comparative law. The objective was to assess the quality of legal decisions and the guarantee of access to justice for animals. The central research question was: “What are the limits and possibilities of extending the application of Habeas Corpus to non-human animals?” The methodology was structured based on four methodological components: approach, theoretical foundation, procedure, and technique. A qualitative approach was adopted. The study was grounded in the theories of animal rights advocates, including Heron Santana Gordilho, Tagore Trajano Almeida Silva, Laura Cecilia Braz, Vicente de Paula Ataíde Junior, and others. The procedural methods used were monographic and historical. As for the technique, indirect documentary research was employed.To facilitate the study, it was divided into three chapters. The first chapter provided a brief discussion on ethology and primatology, contextualizing the cognitive, behavioral, and genetic similarities between human and non-human great apes, highlighting the moral issues of exploiting them in scientific research given their significant similarities.The second chapter presented the challenges of ensuring full access to justice for minority groups, drawing comparisons with the difficulties identified by Cappelletti and Garth, and addressing the challenges of access to justice for sentient beings. It also explored the contributions of international declarations to advancing the recognition of animal rights.Finally, the third and final chapter analyzed Habeas Corpus decisions and proposed a reinterpretation of the waves of legal renewal in animal law to definitively establish animals as subjects of the writ.The study concluded that significant progress has been made in ensuring access to justice for animals. However, these advances are still insufficient to satisfactorily extend the application of Habeas Corpus to sentient beings, as Wise envisioned.